Virando a página na TV: dimensões da leitura em um cenário multiplataforma - Lopes, Giovana Franzolin [UNESP] (2014)
The dissertation investigates the potentials of the terrestrial digital television television as a tool pf stimulation and fomenting for reading. Throughout an exploratory bibliographical research about the history of reading and of television, as well as the habits of Brazilians towards these media, it proposes a study and analysis focusing the convergence among television and the information and communication technologies, as well as book in electronic formats. For that, it investigates the understanding of the publising and television markets based on concepts such as as multiple screens, social TV, information age and digital reading and proposes, at last, some possibilities through which television, specially the terrestrial digital television, may act as a relevant tool to foment reading